System simulation for a novel fetal monitoring methodology. (3rd August 2009) - Mittra, A.K.; Choudhari, N.K.; Zadgaonkar, A.S.
Monitoring the variations of fetal heart rate (FHR) is one of the most important approaches for fetal surveillance. In hospitals, ultrasound-based equipments such as Doppler fetal monitor and cardiotocograph (CTG) are used for FHR monitoring. However, recent studies show that frequent exposure to ultrasound radiations is not recommended for the fetal well-being. Because of this and many other reasons, these instruments are not recommended for prolonged monitoring applications. This work is focused around the development of a computer simulation for a novel fetal home monitoring application, which is also helpful in the management of complex pregnancies. Presented system can record the abnormal FHR and alert the pregnant women to report to a physician. Recorded data is then processed by a novel methodology for deriving results of diagnostic importance. The model has been tested by signals obtained from different pregnant women with varied gestation age. Simulation results show that the technique is suitable and effective for long-term FHR home monitoring application.